2019
DOI: 10.1080/21505594.2019.1635418
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans quorum-sensing molecule farnesol modulates staphyloxanthin production and activates the thiol-based oxidative-stress response in Staphylococcus aureus

Abstract: Microbial species utilize secreted-signaling molecules to coordinate their behavior. Our previous investigations demonstrated a key role for the Candida albicans -secreted quorum-sensing molecule farnesol in modulating Staphylococcus aureus response to antimicrobials in mixed biofilms. In this study, we aimed to provide mechanistic insights into the impact of farnesol on S. aureus within the context of inter-species interactions. To mimic bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 59 publications
0
32
0
3
Order By: Relevance
“…The interaction between C. albicans and the opportunistic pathogen Staphylococcus aureus is another seemingly synergistic fungal-bacterial interaction that was well studied [34,[207][208][209][210][211]. S. aureus commonly colonizes the skin and although the oral microenvironment is a transient one for staphylococci, S. aureus is commonly co-isolated with C. albicans from cases of DS and periodontitis [212][213][214][215].…”
Section: J Fungi 2020 6 X For Peer Review 11 Of 27mentioning
confidence: 99%
“…The interaction between C. albicans and the opportunistic pathogen Staphylococcus aureus is another seemingly synergistic fungal-bacterial interaction that was well studied [34,[207][208][209][210][211]. S. aureus commonly colonizes the skin and although the oral microenvironment is a transient one for staphylococci, S. aureus is commonly co-isolated with C. albicans from cases of DS and periodontitis [212][213][214][215].…”
Section: J Fungi 2020 6 X For Peer Review 11 Of 27mentioning
confidence: 99%
“…Recently, several authors reported that certain quorum-sensing molecules may generate oxidative stress, especially at supraphysiological concentrations, which may have an antifungal effect [ 42 , 43 , 44 , 45 ]. The majority of data concerning fungal quorum sensing molecule-related therapeutic potential derived from C. albicans experiments, and these results cannot be always directly extrapolated to non- albicans species.…”
Section: Fungal Quorum Sensingmentioning
confidence: 99%
“…C. albicans -derived farnesol has also been shown to have an effect on the response of S. aureus to antibiotics in mixed species biofilms. Farnesol exposure results in a significant decrease in staphyloxantin, which is an important virulence factor of this bacterium [ 42 ]. Černáková et al (2018) showed that 200 μM farnesol has an inhibitory effect on C. albicans growth in mixed-species biofilms with Streptococcus mutans [ 93 ].…”
Section: Farnesolmentioning
confidence: 99%
“…C. albicans -secreted β-1,3-glucan was identified as the key constituent providing the bacteria with enhanced drug tolerance [ 11 ] by reducing the diffusion of the antibiotics within the biofilm. Other products by the C. albicans biofilm like extracellular DNA [ 13 ] and farnesol [ 14 ] also raise the drug resistance of S. aureus . Furthermore, C. albicans facilitates the invasion across the mucosal barriers of S. aureus , leading to systemic infection in co-colonized patients [ 9 , 15 ].…”
Section: Introductionmentioning
confidence: 99%